Social Humanism of Madrasah: A Reflection of Indonesian Muslim Intellectuals Establishment - Sunhaji Sunhaji; Moh. Roqib; Nurfuadi Nurfuadi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
This paper describes the existence of Indonesian madrasahs (Islamic schools), which are often considered to be of low quality, but in fact, have contributed a critical knowledge in Indonesia. This article is written using a qualitative method of literature research type. All relevant references to the theme of the discussion will be studied in depth to find new synthesis. Thus, the new paradigm will be built in accordance with the construction of the author's thoughts and collaborated with the existing literature review. We can conclude from this paper that the existence of madrasahs in Indonesia shows the following points. First, madrasahs in Indonesia were established based on a curriculum system that favors the Indonesian people so that Western influences do not bind them. Second, learning in madrasahs is a vital asset in maintaining the purity of Islam in Indonesia. This condition is because the mechanism aims to make students understand religion and local values to uphold unity and integrity. Third, the existence of madrasahs in Indonesia becomes the Indonesian nation's cultural identity and resistance to an established knowledge system without neglecting the rapid development of the times.